A case-control study on factors affecting the incidence of dengue fever in Johor Bahru - R Norli; M.T Azmi (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : Johor Bahru has one of the highest rates of dengue disease in this country in spite of the implementation of COMBI (Communication for Behavioural Impact) in 2001. Methods : To identify factors contributing to this problem, a case control study was conducted, focusing on risk factors such as the weather (rainfall and temperature), environment and sociodemography. Cases were selected from confirmed dengue cases from January to June, 2006. Controls were selected from patients who had no past history of having dengue illness from Health Clinics in Johore Bahru. Both case group and control group were matched by age and sex. All risk factors were analysed using SPSS version 11.5. Results : Results from time-series analysis indicated that the cases of dengue illness were related to changes in the minimum temperature (r =-0.149; p<0.05). It was also shown that the number of dengue illness on a particular week were affected by changes of the minimum temperature at two weeks prior, during that particular week and the week after. As for other risk factors, multivariate analysis indicated that those who were unmarried (Odd ratio (OR): 2.7; 95% Confidence Interval (CI): 1.34 – 5.65), not wearing long sleeve clothes (OR: 5.4; 95% CI: 1.72 – 10.44) and whose homes were not protected with screen windows (OR: 4.2; 95% CI: 1.02 – 29.03) were at higher risk of contracting dengue. Other analysis indicated that the implementation of COMBI improved the knowledge and attitude about combating dengue but did not protect them from the illness. Conclusion : The high rate of dengue illness in Johor Bahru is due to presence of risk behaviour such as lack of personal and home protection which exposed them to the dengue vector, Aedes spp. There is also a need to enhance the COMBI activities, to better protect the population from dengue illness.